Targeting DNA Double-Strand Break (DSB) Repair to Counteract Tumor Radio-resistance - Zhao, Yucui; Chen, Siyu (Current Drug Targets, 2019)
During the last decade, advances of radiotherapy (RT) have been made in the clinical practice of cancer treatment. RT exerts its anticancer effect mainly via leading to the DNA Double-Strand Break (DSB), which is one of the most toxic DNA damages. Non-Homologous End Joining (NHEJ) and Homologous Recombination (HR) are two major DSB repair pathways in human cells. It is known that dysregulations of DSB repair elicit a predisposition to cancer and probably result in resistance to cancer therapies including RT. Therefore, targeting the DSB repair presents an attractive strategy to counteract radio-resistance. In this review, we describe the latest knowledge of the two DSB repair pathways, focusing on several key proteins contributing to the repair, such as DNA-PKcs, RAD51, MRN and PARP1. Most importantly, we discuss the possibility of overcoming radiation resistance by targeting these proteins for therapeutic inhibition. Recent tests of DSB repair inhibitors in the laboratory and their translations into clinical studies are also addressed.
Keywords: radio-resistance